Activities undertaken by Intensive Care Unit Liaison Nurses in Argentina. Issue 2 (March 2017) - Alberto, Laura; Gillespie, Brigid M.; Green, Anna; Martínez, Maria del Carmen; Cañete, Angel; Zotarez, Haydee; Díaz, Carlos Alberto; Enriquez, Marcelino; Gerónimo, Mario; Chaboyer, Wendy
Abstract: Background: The Intensive Care Unit Liaison Nurse (ICULN), also known as an outreach nurse, is an advanced practice nursing role that emerged in the late 1990s in Australia and the United Kingdom (UK). Little is known about this role in less developed economies. Objective: To describe the activities undertaken by ICULNs in Argentina. Methods: Prospective, descriptive, observational, single site study in an Argentinean metropolitan tertiary referral hospital. Adult patients under ICULN follow up were included in the sample. Data on ICULN activities and patients were collected using an established tool developed by The Australian Intensive Care Unit Liaison Nurse Forum. Descriptive statistics were used to summarise the findings. Results: Two hundred patients were visited by the ICULNs during the study period. The mean age of patients was 52.5 years (SD 17.7). Cardiovascular disease ( n = 104, 52%), respiratory disease ( n = 90, 45%) and diabetes ( n = 40, 20%) were the most common comorbidities. 110 (55%) patients had surgical procedures. The primary reasons for ICULN visit were follow up post ICU discharge ( n = 138, 69%) and ward referral ( n = 46, 23%). 136 (68%) patients received up to 3 visits; the remaining 64 (32%) patients received ≥4 visits. In those patients in need of ≥4 visits ICULNs initiated more non-medical treatments (100%), referred to escalate treatment (35%) and to a higher level of care (13.8%) than in those who were visited up to 3 times. Conclusions: This study is the first to document ICULN activity in Argentina using an international framework and data set. These findings can assist with understanding an advanced practice nursing role in Argentina. It may facilitate future comparisons with other contexts and could help managers implementing the role in similar settings. Further investigation will help develop this practice and document its influence on patient outcomes.